2018
DOI: 10.1007/s11908-018-0613-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/Pharmacodynamic Considerations of Beta-Lactam Antibiotics in Adult Critically Ill Patients

Abstract: There is a growing body of literature in adult patients demonstrating that physiological alterations occurring in critically ill patients may limit our ability to optimally dose beta-lactam antibiotics to reach these PK/PD targets. These alterations include changes in volume of distribution and renal clearance with multiple, often overlapping causative pathways, including hypoalbuminemia, renal replacement therapy, and extracorporeal membrane oxygenation. Strategies to overcome these PK alterations include ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 64 publications
3
33
0
Order By: Relevance
“…Since critically ill patients have substantially physiologic changes, the suboptimal concentration of antibiotics was reported [8,15,16]. Thus, high-dose antibiotics should be taken into consideration to achieve better clinical outcomes [6]. Nevertheless, cellular failure due to the individual dysregulated host responses to pro-inflammatory cytokine and alteration of cellular immune function may also progress and might not have been helped by the higher dose of antibacterial [13,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since critically ill patients have substantially physiologic changes, the suboptimal concentration of antibiotics was reported [8,15,16]. Thus, high-dose antibiotics should be taken into consideration to achieve better clinical outcomes [6]. Nevertheless, cellular failure due to the individual dysregulated host responses to pro-inflammatory cytokine and alteration of cellular immune function may also progress and might not have been helped by the higher dose of antibacterial [13,17].…”
Section: Discussionmentioning
confidence: 99%
“…A larger volume of distribution, which is caused by fluid resuscitation and capillary leak syndrome, culminates in subtherapeutic levels of antimicrobial [5]. The fluctuation of renal clearance, such as augmented renal clearance or acute kidney injury, could affect by increasing or decreasing antimicrobials concentrations [6]. In addition, Suwantarat et al reported a high prevalence of MDR gram-negative bacteria in Thailand, including 28.7% for carbapenem-resistant Pseudomonas aeruginosa, 45.2% for extended-spectrum beta-lactamases (ESBL) producers, and 76.3% for carbapenem-resistant Acinetobacter baumannii [7].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
See 1 more Smart Citation
“…Solid organ transplant recipients are vulnerable to sepsis and critical illness, increasing their risk for altered pharmacokinetics (PK) and antimicrobial failure [94][95][96]. β-lactams are hydrophilic, making them susceptible to the physiological effects of such critical illness, which include alterations in the volume of distribution (Vd) secondary to fluid resuscitation, perturbations in serum albumin, and capillary permeability [97][98][99]. Similarly, renal drug clearance may either be augmented or reduced, leading to either an increase or decrease in β-lactam clearance, respectively [97][98][99].…”
Section: Antimicrobial Pharmacokinetics Relevant To Solid Organ Transmentioning
confidence: 99%
“…β-lactams are hydrophilic, making them susceptible to the physiological effects of such critical illness, which include alterations in the volume of distribution (Vd) secondary to fluid resuscitation, perturbations in serum albumin, and capillary permeability [97][98][99]. Similarly, renal drug clearance may either be augmented or reduced, leading to either an increase or decrease in β-lactam clearance, respectively [97][98][99]. The efficacy of βlactams is proportional to the time non-protein-bound drug spends above the MIC, with maximal bacterial killing and clinical efficacy occurring at target concentrations 4 × MIC [100,101].…”
Section: Antimicrobial Pharmacokinetics Relevant To Solid Organ Transmentioning
confidence: 99%